Effect of HA (Hydroxyapatite) content on the microstructure, mechanical and corrosion properties of (Ti13Nb13Zr)-xHA biocomposites synthesized by sparkle plasma sintering. (September 2016) - He, Y.H.; Zhang, Y.Q.; Jiang, Y.H.; Zhou, R.
Abstract: (Ti13Nb13Zr)-HA biocomposites with different HA contents were fabricated by sparkle plasma sintering. The structure, mechanical and corrosion properties of these biocomposites were investigated. The results indicated that the addition of HA to TNZ lead to impede the phase transformation from α -Ti to β -Ti, and produce reaction products which affected the properties. There is a linear relationship ( ρ r = 99.298 − 0.125 W p ) between relative density of biocomposites and HA concentration. The biocomposites exhibited excellent mechanical strength, ensuring better behaviour as implant material. Elastic modulus tests showed that the biocomposites which approximated to that of natural bones were much lower than Ti (or Ti alloys)-HA composites and Ti13Nb13Zr. Biocomposites with 10% of HA performed an optimal corrosion resistant in simulated artificial body fluid. An increase in HA content decreased corrosion resistant owing to the surface micropores and defects induced by reactions between particles and ceramic particle detachment. Highlights: One-step spark plasma sintering (SPS) technique was used to fabricate the metal-ceramic biocomposites. The elastic modulus of biocomposites were in the range of 35.1–52.7 GPa with compression strength of 1005–1528 MPa. Reinforced by HA, the biocomposites performed better corrosion resistance than the TNZ alloy.